The Impact Of Marketing Strategy On Consumer’s Impulsive Buying Behavior On Tiktok Live - Aulia Rahma, Safira; Ridanasti, Erlita (Publisher Cv. Inara, 2023)
Live-streaming shopping is a new form of social commerce that is increasingly popular among Indonesian consumers, especially since the COVID-19 pandemic. However, research on live streaming s-commerce is still in its infancy. This study sheds new light on impulsive purchase behavior in TikTok Live. Based on the stimulus-organism-response (SOR) theory, this study introduces a marketing strategy in the form of 3 retail elements, “People-Product-Place” on scommerce live streaming from the perspective of consumer perception and aims to understand the impact of marketing strategy on impulsive buying behavior of TikTok Live consumers. This study used SEM-AMOS analysis with a purposive sampling method. A sample size of 170 respondents was conducted by distributing questionnaires to TikTok Live users with a shopping experience. The study’s results showed a significant effect on the variable relationship between perceived tiktok anchor attributes on impulsive buying behavior, perceived scarcity on involvement, immersion on involvement, and involvement on impulsive buying behavior. The findings of this paper provide suggestions to online retailers to focus more on increasing the engagement created by anchors, which ultimately makes them make impulse purchases